Paleogeographic evolution of carbonate reservoirs: geological and geophysical analysis at the Albian Campos Basin, Brazil - Castillo Vincentelli, Maria Gabriela [UNESP]; Favoreto, Julia; Roemers-Oliveira, Eduardo (Iop Publishing Ltd, 2018)
An integrated geophysical and geological analysis of a carbonate reservoir can offer an effective method to better understand the paleogeographical evolution and distribution of a geological reservoir and non-reservoir facies. Therefore, we propose a better method for obtaining geological facies from geophysical facies, helping to characterize the permo-porous system of this kind of play. The goal is to determine the main geological phases from a specific hydrocarbon producer (Albian Campos Basin, Brazil). The applied method includes the use of a petrographic and qualitative description from the integrated reservoir with seismic interpretation of an attribute map (energy, root mean square, mean amplitude, maximum negative amplitude, etc), all calculated at the Albian level for each of the five identified phases. The studied carbonate reservoir is approximately 6 km long with a main direction of NE-SW, and it was sub-divided as follows (from bottom to top): (1) the first depositional sequence of the bank was composed mainly of packstone, indicating that the local structure adjacent to the main bank is protected from environmental conditions; (2) characterized by the presence of grainstone developed at the higher structure; (3) the main sequence of the peloidal packstone with mudstones oncoids; (4) corresponds to the oil production of carbonate reservoirs formed by oolitic grainstone deposited at the top of the carbonate bank; at this phase, rising sea levels formed channels that connected the open sea shelf with the restricted circulation shelf; and (5) mudstone and wackestone represent the system's flooding phase.
Keywords: carbonate shoal; grainstone; carbonate facies; permo-porous system